Pelatihan membuat presentasi dengan AI menggunakan Presentations.AI dan ChatGPT bagi Siswa SMK Media Informatika Dasana Indah Tangerang : Pengabdian - Taufik, Ahmad; Sudaryana, I Ketut; Gunadi, Goldie; Tri M, Tupan; Budiyantara, Agus; Doharma, Rouli (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Advances in information technology, particularly artificial intelligence (AI) and generative language models like ChatGPT, can be leveraged in presentation creation. This technology opens up opportunities to automate and simplify creative tasks, including the development of presentation materials. This training aimed to explore the use of AI and ChatGPT to accelerate workflows, improve content quality, and create engaging presentations for students at SMK Media Informatika Dasana Indah, Tangerang. The methods used included case studies and comparative experiments between conventional and AI-based presentation creation. Data was obtained from analyses of quality, design, processing time, and user feedback. The results showed that AI and ChatGPT significantly saved time in developing presentation outlines, ideas, and text drafts. Integrating AI into platforms like Canva or Google Slides also facilitates the selection of professional templates and automated design. However, challenges were identified, such as the limitations of human creativity, the risk of misinterpretation by AI, and the need for content verification.